Private Healthcare Economy: Impact of COVID-19 Restrictions on Elective Healthcare - Zuzana STOLICNA; Michal P. PRZEWLOCKI (Communications of International Proceedings, 2022)
Healthcare providers around the globe have undergone a most demanding period in hundred years. Coronavirus pandemic created significant pressure on both public and private healthcare systems. Small and medium-sized healthcare providers can be more vulnerable to the impacts of the pandemic and pandemic-related restrictions, due to the fact that many of them rely on elective procedures that tend to be most affected. This article examined several studies that analyzed the admissions of patients that underwent elective healthcare to determine the need of further discussion and research. Analysis showed that there is a strong correlation between the pandemic waves, or government restrictions, and the volume of admissions for elective healthcare. We can conclude that elective healthcare was severely impacted, in some cases completely halted, and the need for further research in order to create mitigation strategies can be justified.
Keywords: healthcare; COVID-19; resource allocation